Menstrual Practice Needs Scale (MPNS): Reliability and validity of the Turkish version - Vural, Pınar Irmak; Varışoğlu, Yeliz (Galenos Publishing House, 2021)
BACKGROUND/AIM Menslruol practices have actions undertaken to manage menstrual bleeding including accessing storing and transporting acceptable menstrual materials, changing and disposing of used materials, washing and drying of reusable materials, and cleaning the hands, genitals, and body. This study aims to conduct the reliability and validity study of the Turkish version of the Menstrual Practice Needs Scale (MPNS), which determines the menstrual practices and needs. MATERIAL and METHODS This methodological study was conducted with 446 university students in Istanbul in Turkey from June to July 2020. RESULTS In this study, the mean age of the participants was 19.93 +/- 2.34. The confirmatory factor analysis showed a good fit. Cronbach's a of this scale was 0.78. The test-retest reliability coefficient was r = .661. The content validity index was calculated as 0.89. In this study, the Kaiser Meyer Olkin value was 0.819, which is considered very good. The result of Bartlett's Test of Sphericity was chi(2) = 4,894.399, P < .001 for MPNS. Item-total correlation factor loadings varied from 0.24 to 0.94. According to the item-total correlation, one item was removed. CONCLUSIONS The findings suggest that the Turkish language version of the MPNS is valid and reliable.
Keywords: Menstrual Practice Needs Scale; Nursing Reliability; Validity